Facet Engineering of a Metal–Organic Framework Support Modulates the Microenvironment of Palladium Nanoparticles for Selective Hydrogenation. (19th October 2022) - Gao, Ming‐Liang; Li, Luyan; Sun, Zi‐Xuan; Li, Jia‐Rui; Jiang, Hai‐Long
Abstract: The exposed facets of supported catalysts play a crucial role in catalysis; however, they are usually ignored and related studies remain rare. Herein, we have fabricated a series of sandwich‐structured metal–organic framework composites, denoted ZIF‐8X @Pd@ZIF‐8 (x represents the morphology of ZIF‐8 core, i.e., ZIF‐8C exposing (100) facet, ZIF‐8RD exposing (110) facet, and ZIF‐8TRD exposing mixed (100) and (110) facets), featuring Pd nanoparticles deposited on the specific crystal facets of ZIF‐8 core, for hydrogenation of p ‐chloronitrobenzene. The Pd electronic state is tailored by the ZIF‐8 core, where more electron‐deficient Pd is found in ZIF‐8C @Pd@ZIF‐8 than that in ZIF‐8RD @Pd@ZIF‐8, leading to discriminative adsorption of the −NO2 and −Cl groups of p ‐chloronitrobenzene. Consequently, ZIF‐8C @Pd@ZIF‐8 exhibits excellent activity (97.6 %) and selectivity (98.1 %) to p ‐chloroaniline. This work highlights crystal facet engineering of supports to modulate the microenvironment and electronic state of supported metal nanoparticles, offering a promising avenue to enhanced catalysis. Abstract : Pd nanoparticles supported on a metal–organic framework (MOF) ZIF‐8 with engineered crystal facets were coated with a ZIF‐8 layer, to yield a series of MOF composites. ZIF‐8C @Pd@ZIF‐8, featuring electron‐deficient Pd with a unique microenvironment created by the exposed (100) crystal facet of the ZIF‐8 support, favors adsorption of −NO2 over −Cl, and thus, high activity and selectivity in halonitrobenzene hydrogenation to haloaniline.